Corn, Soybean and Sunflower Production – 2024 Summary - Gretchen F. Sassenrath; Garth Blackburn; Jane Lingenfelser; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2025)
Soybean and corn varieties were tested in replicated field trials at the Southeast Research and Extension Center in Parsons through the Kansas State University variety testing program. In 2024, 16 corn varieties were planted in March 2023. Excess rain led to a very poor stand, and the corn varieties were replanted in mid-June. The late planting led to very poor performance and the test was abandoned. The soybean variety test also failed and was abandoned. Twelve sunflower varieties were tested and harvested. The 2024 growing season was nearly average, but divergent rainfall resulted in flooding early, and long periods of drought in mid- to late summer. Lack of early autumn rains greatly reduced soybean yields. Temperatures throughout the summer were above the 14-year average.
Keywords: crop variety testing; rainfall; growing degree days; extreme degree days